Дикие задачи теории представлений *-алгебр, порожденных образующими и соотношениями - Пирятинская, А.Ю.; Самойленко, Ю.С. (Український математичний журнал, 1995)
Two definitions of wild *-algebras are considered from the point of view of the theory of representations. We present methods for proving the fact that a *-algebra is wild. It is also shown that if a algebra isp-wild, then it isf-wild. The converse statement is not true.